An Examination of the Impact of Computer Skills on the Effective Use of ICT in the Classroom - Az-eddine Khaloufi; Hicham Laabidi (Indonesian Journal of EFL and Linguistics, 2017)
The purpose of this paper is to examine the effect of computer skills on the successful integration of Information and Communication Technologies (ICTs) in Moroccan higher education institutions. Actually, the survival of these institutions in the expansion of modern technologies depends on their readiness to qualify professors and students to implement ICTs for educational objectives. Because of the significant role that computer technologies play in today’s job markets, higher education institutions are required to provide the most appropriate learning and teaching conditions for both professors and students to make effective use of these new technologies within classroom practices. The findings revealed that teachers consider ICTs very essential in their teaching. However, there are low levels of computer technology integration in teaching processes.  This lack of computer technology use in instruction is attributed to several factors. One of these various factors is teachers’ computer skills. It has been found that there are statistically significant differences between professors’ use of ICT with respect to their computer skills, F (4,158) = 32.776, p<0.05.